CFO age and R&D investment of gem-listed companies: The moderating role of female executives - Zhang, Changzheng; Zhao, Yueting (Edelweiss Applied Science and Technology, 2024)
This study focuses on examining the non-linear association between CFO age and enterprise R&D investment while also investigating the moderating role of female executives in effecting such a link between the two in order to promote enterprises’ R&D investment and increase female executives’ participation in corporate. Taking Chinese GEM-listed companies over 2009-2021 consisting of 5891 firm-year observations as the samples, conduct the empirical analysis. The findings indicate that a significant inverted U-shaped relationship exists between CFO age and R&D intensity. Specifically, the curve relationship initially exhibits a positive effect of CFO age on R&D intensity before the age of 44, and after that, it turns out to be negative. Moreover, and quite critically, female executives have a significant negative moderating effect on the inverted U-shaped relationship mentioned above. The findings were confirmed by rich robustness and endogeneity tests. Additionally, further exploration of the relationship between CEO tenure and R&D intensity reveals a similar inverted U-shaped curve but does not find any moderating effect of female executives. Based on these results, the study provides Chinese GEM-listed enterprises with rich theoretical guidance and practical implications to optimize the allocation and motivation of executive talents, the career planning of CFOs, and the decision-making patterns of female executives.